Verplaatsingstijden met het openbaar vervoer in Brussel: de bereikbaarheid van de activiteitenpolen - Kevin Lebrun (Brussels Studies)
With an approach based on the modelling of travel time in the Brussels Region, this article examines the accessibility by public transport of a selection of poles of activity in the Region from different neighbourhoods. Measurements of travel time were thus carried out during the morning rush hour on a weekday, taking all operators into account. The analyses highlight a strong intraregional heterogeneity subject to radial and concentric logic, in particular in relation to transport demand. The significant current and potential contribution of operators other than STIB is also revealed. They also show that close to 30 % of the population of Brussels lives in neighbourhoods with poor accessibility due to location, which raises the question as to an objective aimed at making accessibility more uniform from this point of view. With respect to the factors which determine accessibility by public transport, it appears in particular that car traffic still has a heavy impact on travel time, increasing it by 25 % on average, despite the policies in recent years aimed at protecting or separating public transport from car traffic.